Thickness Optimization of Charge Transport Layers on Perovskite Solar Cells for Aerospace Applications - Doowon Lee; Kyeong Heon Kim; Hee-Dong Kim (Nanomaterials, 2023)
In aerospace applications, SiOx deposition on perovskite solar cells makes them more stable. However, the reflectance of the light changes and the current density decreases can lower the efficiency of the solar cell. The thickness of the perovskite material, ETL, and HTL must be re-optimized, and testing the number of cases experimentally takes a long time and costs a lot of money. In this paper, an OPAL2 simulation was used to find the thickness and material of ETL and HTL that reduces the amount of light reflected by the perovskite material in a perovskite solar cell with a silicon oxide film. In our simulations, we used an air/SiO2/AZO/transport layer/perovskite structure to find the ratio of incident light to the current density generated by the perovskite material and the thickness of the transport layer to maximize the current density. The results showed that when 7 nm of ZnS material was used for CH3NH3PbI3-nanocrystalline perovskite material, a high ratio of 95.3% was achieved. In the case of CsFAPbIBr with a band gap of 1.70 eV, a high ratio of 94.89% was shown when ZnS was used.